Pengaruh Corporate Social Responsibility Disclosure Terhadap Financial Performance dengan Good Corporate Governance sebagai Variabel Moderasi - Rosid, M Abdul; Marsono (Jurnal Ilmiah Aset, 2024)
This research aims to analyze and obtain empirical evidence on the influence of corporate social responsibility (CSR) disclosure on financial performance in non-financial companies listed on the Indonesia Stock Exchange during the period 2018-2022, with corporate governance as a moderating variable. Corporate governance (CG) is measured using indicators of audit quality and the composition of independent board commissioners. This research utilizes secondary data from 859 non-financial companies listed on the Indonesia Stock Exchange during the period 2018-2022. The sampling method employed is purposive sampling, resulting in a total sample of 38 non-financial companies selected based on predefined criteria. The analytical method used is Moderated Regression Analysis (MRA). The findings indicate that CSR has a negative impact on ROE, while CSR does not affect EPS. Audit quality as an indicator of CG does not moderate the relationship between CSR and financial performance. However, the indicator of the composition of independent board commissioners moderates the relationship between CSR and financial performance measured by ROE, though it does not significantly affect financial performance measured by EPS